2020
DOI: 10.1016/j.ajog.2020.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal depressive and anxiety symptoms of pregnant women during the coronavirus disease 2019 outbreak in China

Abstract: BACKGROUND: On January 20, 2020, a new coronavirus epidemic with human-to-human transmission was officially declared by the Chinese government, which caused significant public panic in China. In light of the coronavirus disease 2019 outbreak, pregnant women may be particularly vulnerable and in special need for preventive mental health strategies. Thus far, no reports exist to investigate the mental health response of pregnant women to the coronavirus disease 2019 outbreak. OBJECTIVE: This study aimed to exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

58
648
22
36

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 589 publications
(824 citation statements)
references
References 19 publications
58
648
22
36
Order By: Relevance
“…The present study ndings show that the prevalence of postpartum depressive and post-traumatic stress symptoms among the women experiencing childbirth during the Covid-19 pandemic was higher than that reported in previous studies before the pandemic. Literature data report that approximately 10-16% of women met major depression's criteria at 3 months postpartum [24,[33][34][35][36]. The ndings for our cohort (30.7%) are shared by a recent study that reported that 30% of the mothers who delivered during the Covid-19 pandemic had a global EPDS score > 12 compared with 11.9% in an antecedent matched group of postpartum women [36].…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…The present study ndings show that the prevalence of postpartum depressive and post-traumatic stress symptoms among the women experiencing childbirth during the Covid-19 pandemic was higher than that reported in previous studies before the pandemic. Literature data report that approximately 10-16% of women met major depression's criteria at 3 months postpartum [24,[33][34][35][36]. The ndings for our cohort (30.7%) are shared by a recent study that reported that 30% of the mothers who delivered during the Covid-19 pandemic had a global EPDS score > 12 compared with 11.9% in an antecedent matched group of postpartum women [36].…”
Section: Discussionsupporting
confidence: 50%
“…Recent literature regarding the Covid-19 outbreak has largely focused on mental health and psychological needs during pregnancy. Following o cial statements on human-to-human transmission of SARS-CoV-2, there was a clinically signi cant rise in the prevalence of depressive and anxiety symptoms among pregnant women in their third trimester [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…In the time of epidemic crisis, women after childbirth are exposed to several of the above-mentioned consequences (social isolation, higher life stress), which may worsen their mental health, and the existing psychosocial resources may not be su cient to cope with the process of transition to motherhood, which can result in the development / intensi cation of depressive symptoms. Previous studies [9,10] described the effects of the covid-19 epidemic on the depression and anxiety levels of pregnant women. Recent assessment of depression symptoms with the Edinburgh Postnatal Depression Scale revealed signi cantly higher rates of depressive symptoms among pregnant women assessed after the declaration of covid-19 epidemic in comparison to women assessed in pre-epidemic period [10].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies [9,10] described the effects of the covid-19 epidemic on the depression and anxiety levels of pregnant women. Recent assessment of depression symptoms with the Edinburgh Postnatal Depression Scale revealed signi cantly higher rates of depressive symptoms among pregnant women assessed after the declaration of covid-19 epidemic in comparison to women assessed in pre-epidemic period [10]. However, there are no reports on the occurrence of severe depressive symptoms among women in the postpartum period during epidemic crisis.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, 47% of participants thought that social media was not being used e ciently for informing the society. Wu Y et al reported apart from the bene ts of social media, it causes extreme fear, isolation, fear of death, and proneness to depression among the society, especially during the time of lockdown [14].…”
Section: Resultsmentioning
confidence: 99%